The interaction of sodium and potassium ions on some morpho-physiological traits of Jam and Piroz chickpea cultivars (Cicer arietinum L.) - Mostafa Shamsabadi; Ali Ganjeali; Mehrdada Lahooti; Elham Amjadi (پژوهش‌های حبوبات ایران)
IntroductionChickpea is one of the most important sources of protein in human diet. The significance of salinity resistant genotypes for growth and development has been recognized in saline environments. Recognition of salin resistant genotypes is an important and economical goal to improve chickpea performance in saline soils. Under salinity stress, destruct chloroplast structure and decreases photosynthetic pigments. Osmotic regulations induced by changes in nitrogen metabolisms in via formation of prolin. Prolin, as a osmosis regulator between cytoplasm and vacoel, by preventing denaturation of protein structures, protects cellular structure against free radicals. Calcium is an essential element to improvement of injurey of salinity stress in plant. Calcium is substitute other cations in plasma membrane. Plasma membrane is strongly sensitive to salinity stress specialy while the the calcium concentration is low. Studies show that the ion accumulation site in saline tolerant plants is vacuoles. Due to ameliorative role of calcium in saline stress, the present study was conducted to investigate the response of common chickpea cultivars to different concentrations of Na+ and Ca2+ ions in flowering stage. Materials and MethodsIn order to investigate the effect of calcium on amelioration of salinity damage, a factorial experiment as completely randomized design with three replications was conducted by five sodium chloride )0, 3, 6, 9, 12 dS/m( and two calcium sulfate levels )0 and 5 mM) in phytotron condition in Research Center for Plant Sciences, Ferdowsi University of Mashhad. Each experimental unit was a pot with 2 liter that contain mix of soil garden and silt. After 6 weeks plants were extracted and morphological traits such as plant height, leaf area, root length, dry weight of shoot, leaf and root, root area and physiological traits such as SPAD number, membrane stability, leaf relative water content, and biochemical traits such as Sodium, potassium and calcium, proline were measured. Data analysis was performed by Mstat-C and used Duncan's multiple domain test (P <0.05) to compare means. Results and DiscussionThe results showed that salinity significantly increased the sodium and proline contains of leaves and roots. Na+ concentration in 9 dS/m salinity, significantly decreased in both cultivars. Also, salinity increased the potassium content of leaf and calcium content of root and shoot. Leaves potassium content under 9-12 dS/ m salinity, calcium only under 12 dS/m salinity and root calcium content under 9 to 12 dS/m compared to control significantly decreased. Studies have shown in high salinity concentrations, the caspary ring can not inhibit the arrival of sodium ions into the tissues plant and ends with leaves through the unilateral flow of wood. In toxic contaminants of Na+, the glutamateligase enzyme activity increases to convert glutamine to proline. In saline environments, application of calcium is required to synthesis of osmotic protection compounds such as proline, to biochemical compatibility of plant. Salinity increases proline product and decreases the synthesis of chlorophyll precursor. Also, chlorophyll content decreases due to increased chlorophylase activity. The SPAD number and the membrane stability index significantly decreased at 6 to 12 dS/m salinity. In both cultivar, amilorateing effect of calcium under lower salinites (less than 6 dS/m) was higher than the high levels of salinity. For Jam cultivars, the use of calcium sulfate significantly increased the membrane stability index compared to control (no calcium application) in all salinity levels. In salt stress conditions, the capacity of water absorption in plant decreases and gradually salt accumulates in plant environment. Research has shown that salinity decreases the photosynthesis by reducing stomatal conductance. In this way, salinity stress usally increase number and dimensions of stomata per leaf area. The results of means comparison showed that plant height under 6-12 dS/m salinites, significantly decreased compared to control. The cause of less plant growth in high concentrations of Na+ is joint effects of osmotic stress, ion toxicity and nutrient concentrations, which limits the amount of available water of the plant and reduces root water absorption.  ConclusionSalinity has a great effect on the growth of crops such as chickpea. High concentrations of Na+ reduced the growth of both chickpea cultivars (Jam and Pirooz) by increasing the permeability of the membrane. Calcium treatment in lower salinity levels could improved the relative growth of the plants and it is belive that calcium acts as a moderator salinity leveles.